Balancing organizational structure dimensions for enhanced financial performance in Ghana’s banking sector - Nunoo, Evans; Jagannathan, Uday K. (The Economics and Finance Letters, 2025)
This study investigates how the structural dimensions of centralization, formalization, and specialization, both individually and in combination, influence return on equity (ROE) in Ghanaian commercial banks. It clarifies whether a balanced mix outperforms across-the-board intensification. Survey data from 400 employees across ten diverse banks were analyzed using partial least squares structural equation modeling after confirmatory factor analysis confirmed construct reliability and validity. Direct and moderated paths were assessed with bias-corrected bootstrapping. Centralization (β = 0.943, p < 0.01), formalization (β = 0.614, p < 0.05), and specialization (β = 1.391, p < 0.10) each raise ROE. The centralization × formalization interaction is negative and significant (β = -0.074, p < 0.05), whereas the other two-way interactions and the three-way term are nonsignificant. Profitability improves when each dimension is optimized independently; simultaneously concentrating authority and codifying rules can dampen adaptability and erode returns. Structural balance, not wholesale layering, best supports performance in turbulent, regulated settings. Bank leaders should centralize compliance-critical decisions, formalize core risk controls, and deploy specialist teams for complex tasks, while avoiding heavy centralization combined with rigid procedures. Regulators could add a “structural-balance” lens to supervisory scorecards to encourage resilient yet agile governance.